Novel α-tocopherol–ferrocene conjugates for the specific delivery of transgenes in liver cancer cells under high serum conditions. (22nd October 2021) - Asfiya, Rahmat; Maiti, Bappa; Kamra, Mohini; Karande, Anjali Anoop; Bhattacharya, Santanu
Abstract : Selective liposomal gene transfection in liver cancer cells under high serum condition. Abstract : The delivery of therapeutic genes to a specific organ has drawn significant research attention. Among the pool of various delivery vectors, cationic liposomes (non-viral) are potential candidates for delivering therapeutic genes due to their low immunogenic response. Here, we have developed novel ferrocene-conjugated cationic tocopheryl aggregates as non-viral vectors. These formulations can transfer a reporter gene (pGL3; encoded for luciferase protein) specifically to liver cancer cells (HepG2 and Huh7) instead of non-hepatic cancer cells, such as Caco-2 (human colon carcinoma) and HeLa (cervical cancer) cells. The transfection efficiency (TE) of the optimum liposomal formulation is more significant than commercially available Lipofectamine 2000 (L2K). Notably, it retains its TE under high serum conditions (up to 50% FBS). A coupled effect from conjugated ferrocene and tocopherol in the cationic liposomal formulation might be responsible for the cell-specific delivery and higher serum compatibility. Therefore, the present proposed delivery system may provide a platform for further progress in terms of developing hepatotropic gene delivery systems.